The Role of Auxin and Gibberellin in Controlling Lignin Formation in Primary Phloem Fibers and in Xylem of Coleus blumei Stems - Aloni, Roni (1990)
The hypothesis that auxin (IAA) and gibberellic acid (GA(3)) control the formation of lignin is confirmed for the primary phloem fibers and for the secondary xylem in the stem of Coleus blumel Benth. Indoleacetic acid alone, or a combination of high IAA/low GA(3) (w/w), induced short phloem fibers with thick secondary walls, that contained lignin rich in syringyl units (high ratio of syringyl/guaiacyl). On the other hand, a combination of high GA(3)/low IAA (w/w), which promoted the differentiation of long phloem fibers with thin walls, decreased the relative content of the syringyl units (low syringyl/guaiacyl ratio). In the secondary xylem, these hormonal treatments yielded only slight changes in the noncondensed monomeric guaiacyl units, confirming the relative stability of the guaiacyl lignification pattern in this tissue. In the xylem, indoleacetic acid alone, or a combination of high IAA/low GA(3) induced lignin poor in syringyl units (low syringyl/guaiacyl ratio). A combination of high GA(3)/low IAA promoted a relatively slight increase in syringyl yield, indicating greater responsiveness of the syringyl lignification pattern to growth regulators. The possible functional and technological significance of our results is discussed.